Lignin Removal and Cellulose Digestibility Improved by Adding Antioxidants and Surfactants to Organosolv Pretreatment of Sugarcane Bagasse - Schmatz, Alison Andrei [UNESP]; Masarin, Fernando [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2021)
Annually, tons of sugarcane bagasse are generated in the sugar and alcohol industries. This biomass has great potential in the use of converting cellulose into glucose, an energy currency for various biotechnological processes. However, lignin content is a limiting factor in cellulose accessibility. This study aimed to improve lignin removal by evaluating the additive's effect on biomass pretreatment. The additives were tert-butylhydroquinone, 3-tert-butyl-4-hydroxyanisole, methyl 3,4,5-trihydroxybenzoate; surfactants Tween 20, Tween 80, and dimethyl sulfoxide (DMSO). The antioxidants collaborated with lignin removal; the 3-tert-butyl-4-hydroxyanisole reached 71% of lignin removal. Inherent to the pretreatment, tert-butylhydroquinone showed 23.53% and 89.54% of cellulose and hemicellulose removal, respectively. Dioxane extraction compounds from the pretreated biomass showed an increased amount using additives, suggesting more compounds adsorbed on the material surface. All the antioxidants/surfactants applied to the organosolv pretreatment improved enzymatic hydrolysis, reaching 98.9% cellulose into glucose conversion (Tween 80). The use of chemical compounds during pretreatment beneficed the removal of lignin from biomass and consequently the cellulose hydrolysis.
Keywords: Cellulose; Pseudo-lignin; Surfactants; Tween 80